2006
DOI: 10.2136/sssaj2004.0339
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Responses to Potassium‐Based Black Liquor from Straw Pulping

Abstract: Sodium-based black liquor from fiber pulping for papermaking creates challenging waste disposal issues. By substituting NaOH with KOH in the pulping process, the resulting black liquors may be land applied as an environmentally beneficial disposal alternative. Incubation studies examined the effect of KOH-based black liquor on soil pH, electrical conductivity (EC), microbial biomass, CO 2 evolution, and soil enzyme activities in a silt loam soil. Amended soils with black liquor at rates up to 67.2 mL kg 21 soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Increased water holding capacity and electrical conductivity in contaminated soil may be due to the accumulation of organic waste such as amino acid residues, acids and alkalis in the paper industry effluents. The results were in conformity with the studies of Sparling et al (18), Narasimha et al (2), Poonkothai and Parvatham (19), and Xiao et al (20) had increased electrical conductivity in soil contaminated by the effluents of dairy, cotton ginning, automobile, and black liquor for straw pulping industries, respectively. The parameters like organic matter percentage, total nitrogen, phosphorus, potassium were higher in test soil than the control soil.…”
Section: Resultssupporting
confidence: 91%
“…Increased water holding capacity and electrical conductivity in contaminated soil may be due to the accumulation of organic waste such as amino acid residues, acids and alkalis in the paper industry effluents. The results were in conformity with the studies of Sparling et al (18), Narasimha et al (2), Poonkothai and Parvatham (19), and Xiao et al (20) had increased electrical conductivity in soil contaminated by the effluents of dairy, cotton ginning, automobile, and black liquor for straw pulping industries, respectively. The parameters like organic matter percentage, total nitrogen, phosphorus, potassium were higher in test soil than the control soil.…”
Section: Resultssupporting
confidence: 91%
“…Similarly, other studies reported that organic fertilizer improved soil productivity and fertility, which improved yield and quality of crops (Whalen et al, 2000;Maerere et al, 2001;Vanek et al, 2003). The soil treated with manure was found to be loose, which probably provided adequate aeration into the soil and improved soil microbial activities (Xiao et al, 2006). Higher soil microbial activities may release nutrients from the farmyard manure as well as soil for better plant growth.…”
Section: Methodsmentioning
confidence: 82%
“…In addition, chemicals may destroy many species of plants, insects, fishes and soil microorganisms (Fantroussi et al, 1999). Therefore, utilization of farmyard manure in agriculture is recommended for retaining productivity of problem soils, reducing the usages of chemical fertilizer, improving economy in agriculture and minimizing environmental problems (Sharifuddin and Zaharah, 1991;Neera et al, 1999;Whalen et al, 2003;Xiao et al, 2006). Turmeric is a horticultural root-crop that is important not only as a spice and cosmetic, but also as a medicinal plant worldwide (Hermann and Martin, 1991;Osawa et al, 1995;Sugiyama et al, 1996;Nakamura et al, 1998;Ishimine et al, 2003;Hossain et al, 2005a, b).…”
mentioning
confidence: 99%
“…Xiao et al [29] examined the effect of KOH-based black liquors on the soil pH, the electrical conductivity (EC), the microbial biomass, the evolution of carbon dioxide, and the soil enzyme activity in a silt loam soil. Results for treated soils with up to 67.2 mL/kg black liquor have indicated that such applications would not cause salinity problems, with an EC increase in soil to a minimal level of 1.04 dS/m.…”
Section: Scale-up Of Bagasse Pulping and Assessment Of The Feasibilitmentioning
confidence: 99%